Teaching Reading and Summarising; a Lesson Focus on Reading and Summary Writing Aimed to EAP Intermediate Students - Hassan, Shaima A.; Kareem, Deman K. (Humanities Journal of University of Zakho, 2016)
Academic writing has a significant role in the area of higher education, both in students’ understanding of course content and the consequent assessment of students’ knowledge. This research aims to present a brief overview of reading and summary writing then an evaluation of teaching materials being used in a lesson on reading and summary writing together with a detailed commentary of the lesson plan will be presented.